SISTEM FUZZY METODE SAW PEMBERIAN BEASISWA PADA MAHASISWA STMIK TUNAS BANGSA BANDAR LAMPUNG - Alhibarsyah Alhibarsyah (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
The scholarship is a form of giving the material, besides being able to encourage the students to be more active, to support the progress of the education world, to sharpen themselves to become a qualified student, and also to provide the relief in paying tuition fee for the students. STMIK Tunas Bangsa holds a scholarship program for outstanding and underprivileged students by fulfilling the requirements that must be met. This is where the campus conducts selection to determine who is eligible to receive the scholarship. In the process of selection of scholarship recipients is needed a method of decision-making scholarship. One of the methods that can be used for decision support systems is by applying the Fuzzy MADM (Multiple Attribute Decission Making) method. To perform the calculation on this method using SAW (Simple Additive Weighting) method. This method is chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is that eligible to receive scholarship based on the criteria specified. Keywords : Scholarships, Fuzzy, SAW, Decisions, Criteria